Investigation of the effect of cochlear implantation on tinnitus, and its associated factors. (2nd June 2020) - Hsieh, Wen-Hui; Huang, Wen-Ting; Lin, Hung-Ching
Abstract: Background: Many studies have focused on the suppressive effects of cochlear implants (CIs) on loudness of tinnitus. Aims/objective: This study aimed to examine the effects of CIs and their activation on changes in loudness and tinnitus and explore other factors associated with this effect. Material and methods: We recruited 26 CI recipients according to specific criteria. Participants asked to complete tinnitus questionnaires, while the CI was kept on and at 30 min after the CI was turned off. Tinnitus improvement after CI was tested using Wilcoxon signed rank tests, and correlation was tested using Spearman's rank correlation coefficients and multiple linear regression. Results: After CI, tinnitus reduced from 62% to 46%. Total and partial reduction in tinnitus was seen in 76% subjects with pre-CI tinnitus. However, 6% of the subjects had tinnitus since birth, and none showed worsening tinnitus. The average THI score while the CI on was significantly lower than that CI off. Conclusions: Post-CI tinnitus improvement was seen in 76% of those with pre-CI tinnitus; however, the low risk of new or aggravating tinnitus should be considered, and reasonable expectations for tinnitus reduction should be built into the pre-CI assessment.